Penataan Jalur Pedestrian Koridor Jl. Aroepala sampai dengan Jl.Letjen Hertasning, Kota Makassar - Andi Awisti Akrar; Ananto Yudoyono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
In general, pedestrian lanes on the corridor road section Aroepala Street and Letjen Hertasning Street has not fulfilled the expectations of its users, due to the width of the pedestrian lane that has not met the standards, the incomplete street furniture, and the use of parking areas on the shoulder of the road exacerbating pedestrian inconvenience in the corridor of the area. The purpose of this planning is to identify the performance of pedestrian lanes and pedestrian perceptions as well as arrange direction for handling pedestrian lanes on these roads. This plan begins with a study using Level of Service (LOS), Importance Performance Analysis (IPA) and correlation analysis. Preparation of directives for handling is done based on LOS calculation and priority level of pedestrian lines. The results of this study are the level of pedestrian service on Street Letjen Hertasning is classified as LOS B and LOS C while for Aroepala Street has no pedestrian path so the LOS value cannot be determined. The level of suitability between the level of importance and satisfaction of pedestrians to the pedestrian lane in the study location is classified as inappropriate. This can be seen based on the percentage level of conformity, where the four segments in the variables of comfort, safety and attractiveness have a level of conformity below 100%. The direction of planning that is carried out is the provision of priority indicators for pedestrian lane facilities using illustrated plan drawings and handling maps in the form of improvements and new development.